2003
DOI: 10.1177/0734242x0302100603
|View full text |Cite
|
Sign up to set email alerts
|

Household food waste to wastewater or to solid waste? That is the question

Abstract: Decision makers need sound analyses of economic and environmental impacts of options for managing household food waste. Food waste impacts public health (it rots, smells, and attracts rodents) and costs (it drives collection frequency). A life cycle inventory is used to quantify total materials, energy, costs and environmental flows for three municipal solid waste systems (collection followed by compost, waste-to-energy or landfill) and two wastewater systems (kitchen food waste disposer followed by rural on-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Several previous LCAs of food waste management systems have found that incineration, anaerobic digestion and composting all can result in net avoidance of GWP (Fruergaard and Astrup, 2011;Kirkeby et al, 2006;Smith et al, 2001;Møller et al, 2009;Boldrin et al, 2009), while other studies have come to the conclusion that the same management practices can result in a net contribution to GWP (Baky and Eriksson, 2003;Diggelman and Ham, 2003;Lee et al, 2007). The reason for this can be found in differing assumptions of for example energy and or nutrient recovery, technology choice (i.e.…”
Section: Waste Management Systemmentioning
confidence: 91%
“…Several previous LCAs of food waste management systems have found that incineration, anaerobic digestion and composting all can result in net avoidance of GWP (Fruergaard and Astrup, 2011;Kirkeby et al, 2006;Smith et al, 2001;Møller et al, 2009;Boldrin et al, 2009), while other studies have come to the conclusion that the same management practices can result in a net contribution to GWP (Baky and Eriksson, 2003;Diggelman and Ham, 2003;Lee et al, 2007). The reason for this can be found in differing assumptions of for example energy and or nutrient recovery, technology choice (i.e.…”
Section: Waste Management Systemmentioning
confidence: 91%
“…FWD water consumption below 5 L/person/day has been reported in a wide range of studies (e.g. (De Koning and Van Der Graaf, 1996;Diggelman and Ham, 2003;Marashlian and El-Fadel, 2005;Nilsson et al, 1990;Rosenwinkel and Wendler, 2001). Nilsson et al (1990) analysed household practices upon installation and determined that the use of FWDs coincided with peak sewer flows i.e.…”
Section: Fwds and Water Consumptionmentioning
confidence: 94%
“…are to be considered [14]. Some recent papers provide a detailed methodology to consider these issues in advanced LCA studies [15].…”
Section: Initial Auditmentioning
confidence: 99%